2019
DOI: 10.1016/j.neuropharm.2019.107794
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as positive allosteric modulators of α7 nicotinic receptors

Abstract: The use of positive allosteric modulators (PAM) of α7 nicotinic receptors is a promising therapy for neurodegenerative, inflammatory and cognitive disorders. Flavonoids are polyphenolic compounds showing neuroprotective, anti-inflammatory and pro-cognitive actions. Besides their well-known antioxidant activity, flavonoids trigger intracellular pathways and interact with receptors, including α7. To reveal how the beneficial actions of flavonoids are linked to α7 function, we evaluated the effects of three repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(84 citation statements)
references
References 123 publications
(252 reference statements)
4
76
4
Order By: Relevance
“…Radioligand binding experiments indicate that apigenin and other flavonoids does not alter [ 125 I] α-bungarotoxin binding suggesting that these compounds act as allosteric modulators of the α7-nACh receptor. These results confirm earlier findings with genistein and quercetin [ 17 , 18 , 19 ], and identify apigenin, and other flavonoids, as likely PAM of the human α7-nACh receptor. The PAMs are promising therapeutic agents since they maintain the temporal and spatial characteristics of the endogenous activation of the receptor and are usually more selective than agonists [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Radioligand binding experiments indicate that apigenin and other flavonoids does not alter [ 125 I] α-bungarotoxin binding suggesting that these compounds act as allosteric modulators of the α7-nACh receptor. These results confirm earlier findings with genistein and quercetin [ 17 , 18 , 19 ], and identify apigenin, and other flavonoids, as likely PAM of the human α7-nACh receptor. The PAMs are promising therapeutic agents since they maintain the temporal and spatial characteristics of the endogenous activation of the receptor and are usually more selective than agonists [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further studies with more complex phytochemicals identified curcumin and its metabolites as positive allosteric modulators (PAM) of α7 nACh receptor [ 14 , 15 , 16 , 17 ]. Importantly, some of the flavonoid-group phytochemicals, such as genistein and quercetin, were recently shown to act as a PAM of α7 nACh receptor [ 17 , 18 , 19 ]. In the present study, we have investigated the effects of a panel of polyhydroxy flavonoids that are the products of differently substituted 5,7-dihydroxy-4H-chromen-4-one structural skeleton ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In non-treated cells and in the absence of PP2, channel activity appeared mainly as brief and isolated openings or as several openings in quick succession, known as bursts, which correspond to the activation episode of a single receptor molecule (Fig. 1 a) [ 32 , 38 ]. Open and burst duration histograms were described by two exponential components, with mean durations of the slowest components of 0.32 ± 0.07 ms and 0.48 ± 0.13 ms ( n = 17), respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Single channels were recorded in the cell-attached patch configuration [ 32 , 38 ]. The bath and pipette solutions contained 142 mM KCl, 5.4 mM NaCl, 1.8 mM CaCl 2 , 1.7 mM MgCl 2 and 10 mM HEPES (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation